The Quality of Working Life of Newly Graduated Nurses - Phimchaisai, Punyanut; Taewaphokinkul, Muntana; Pumcharoen, Rungaroon (Journal of The Royal Thai Army Nurses, 2021)
The purposes of this descriptive research were to study and compare the quality of working life of newly graduated nurses. The samples were 251 newly graduated nurses from a private university in Nakhon Pathom Province. The data were collected by using 2 sets of questionnaires: demographic data and the quality of working life. which contains 8 aspects. The questionnaires were tested for content validity, IOC was .92 and Cronbach’s alpha coefficient was .96 respectively. The data were analyzed by using frequency, percentage, mean, standard deviation, and t-test (p < .05) The findings of this research were as follows: 1. The level quality of working life of newly graduated nurses, classified in each aspects and the overall, found that the quality of working life was at a high level as follows: the aspect with the highest average was social relevance of work life ( = 4.24, SD = 0.59), the followed in safe and healthy working conditions ( = 4.21, SD = 0.55), the lowest average was the adequate and fair compensation ( = 3.90, SD = 0.72), and the overall quality of working life was a high level ( = 4.13, SD = 0.50) 2. The comparison of the differences between the average quality of working life of newly graduated nurses in the aspect of overall quality of working life with demographic data, it was found that factors with averaging scores were statistically significant, which were males had a higher average score than females (t = 2.103, p = 0.036). The average of the salary >30,000 Baht. had higher scores than ≤ 30,000 Baht. (t = -2.317, p = 0.023), and the number of holidays per month > 8 days, the average score was higher than ≤ 8 days (t = -2.301, p = 0.032).